Upconverting nanoparticles in ultrasensitive detection of cardiac troponin I - Raiko, Kirsti (fi=Turun yliopisto|en=University of Turku|, 2023)
Development of high-sensitivity immunoassays is a continuous interest in medical diagnostics, especially in the case of such diseases where higher sensitivity analyte measurements improve the prognosis of treatment. One such analyte is cardiac troponin I, used for detection of cardiac events. One of the key factors determining immunoassay sensitivity is the reporter, which labels the analytes in the assays and produces the measurable signal. Upconverting nanoparticles (UCNPs) are promising candidates for reporters in sensitive immunoassays. Their unique ability to convert near-infrared light into higher energy visible light by stacking photons, producing emission exhibiting anti-Stokes shift. As no other natural materials are capable of the process, measurement of UCNPs can be designed to completely dismiss any background signal originating from autofluorescence. However, reaching the maximal sensitivity they theoretically enable has been hindered by their tendency to non-specifically bind to solid surfaces in assays and to each other, forming nanoparticle clusters of varying sizes. The extent of these tendencies has been linked to the surface chemistry of the UCNPs. The aim of this thesis was to study the surface chemistry of UCNPs and apply them as reporters in different immunoassay technologies for detection of cTnI. During the research, surface coating of UCNPs with poly(acrylic acid) was studied and successfully improved, leading to reduced non-specific binding and cluster formation tendency. The performance of the UCNPs with the novel surface was compared to other surface chemistry approaches in microtiter plate assays utilizing either analog or digital readout method, and a lateral flow assay. Another aim was to develop the used assay technologies utilizing upconversion to reach extreme sensitivities. Reagents and conditions in analog microtiter plate assay for cTnI were thoroughly investigated to fine-tune the performance, and the limit of detection (LoD) reached an unprecedented low value of 0.13 ng/L for an analog assay. In addition, a mechanical actuator for automation of a lateral flow assay for cTnI was fabricated via 3D-printing, and when combined with the improved UCNPs, an LoD of 1.5 ng/L was reached, bringing high-sensitivity pointof- care detection of cTnI a step closer to reality. KEYWORDS: cardiac biomarker, luminescence, nanoparticle monodispersity

Herkkien immunomääritysmenetelmien kehitys on jatkuvan kiinnostuksen aiheena diagnostiikan tutkimuksessa. Herkät biomerkkiainetestit ovat haluttuja etenkin sydänkohtauksen kaltaisissa tiloissa, jossa merkkiaineen pitoisuus verenkierrossa kasvaa samalla, kun hoitoennuste heikkenee. Yksi merkittävimmistä immunomääritysten herkkyyteen vaikuttavista tekijöistä on määritysleima, joka sitoutuu analyyttiin ja tuottaa mitattavan signaalin. Käänteisviritteisten nanopartikkelien (engl. upconverting nanoparticles, UCNP) kyky muuntaa matalaenergistä viritysvaloa korkeaenergiseksi emissioksi tekee niistä lupaavan määritysleiman herkkiin immunomäärityksiin, koska UCNP:iden signaalin mittaus voidaan tehdä niin, ettei autofluoresenssista koituvaa taustasignaalia havaita, mahdollistaen äärimmäisen herkät immunomääritykset. UCNP:iden taipumus sitoutua epäspesifisesti erilaisiin pintoihin ja muodostaa erikokoisia kasaumia on hidastanut niiden käyttöönottoa herkkinä immunomääritysleimoina. Tämän ominaisuuden on osoitettu riippuvan voimakkaasti partikkelien pintakemiasta. Tämän tutkimuksen tavoite oli tutkia UCNP:iden pintakemiaa ja hyödyntää niitä määritysleimoina erilaisissa cTnI:tä havaitsevissa immunomäärityksissä. Tutkimuksessa selvitettiin UCNP:iden poly(akryylihappo) (PAA) -pinnoituksen onnistumiseen vaikuttavia tekijöitä ja onnistuttiin merkittävästi vähentämään PAA-pintaisten UCNPeiden epäspesifistä sitoutumista ja kasautumistaipumusta. Näitä UCNPleimoja verrattiin muulla tavoin pinnoitettuihin UCNP-leimoihin mikrotiitterilevypohjaisessa immunomäärityksessä käyttäen joko analogista tai digitaalista mittausmenetelmää, sekä lateraalivirtausmäärityksessä. Toinen tavoite oli kehittää käytettyjä määritysmenetelmiä äärimmäisten herkkyyksien saavuttamiseksi. Mikrotiitterilevymäärityksen reagenssit ja toteutusmenetelmä tutkittiin tarkoin ja hienosäädettiin. Tällä tekniikalla saavutettiin 0,13 ng/L havaitsemisherkkyys cTnI:lle, mikä on ennätyksellistä analogisissa mikrotiitterilevymäärityksissä. Lisäksi suunniteltiin mekaaninen 3D-tulostettu laite automatisoimaan cTnI:tä havaitseva lateraalivirtausmääritys. Yhdistettynä paranneltuihin PAA-UCNP:ihin, saavutettiin 1,5 ng/L havaitsemisherkkyys, mikä tuo äärimmäisen herkät cTnI:n vieritestausmenetelmät askeleen lähemmäs todellisuutta. ASIASANAT: sydänmerkkiaine, luminesenssi, nanopartikkelien yksittäisyys